Engineering Behaviour of Rocks - Farmer, Ian W. author. aut Link
VII, 208 p. 112 illus.
Keywords: The first edition of this book was received more kindly than it deserved by some, and with some scepticism by others. It set out to present a simple, concise and reasonably comprehensive introduction to some of the theoretical and empirical criteria which may be used to define rock as a structural material. The objectives - reinforced by the change in title - remain the same, but the approach has been changed considerably and only one or two sections have been retained from the first edition. The particular aim in this edition is to provide a description of the mechanical behaviour of rocks, based firmly upon experimental data, which can be used to explain how rocks deform, fracture and yield, and to show how this knowledge can be used in design. The major emphasis is on the behaviour of rocks as materials, although in the later chapters the behaviour of discontinuities in rocks, and the way in which this can affect the behaviour of rock masses, is considered. If this edition is an improvement on the first edition it reflects the debt lowe to numerous people who have attempted to explain the rudiments of the subject to me. I should like to thank Peter Attewell and Roy Scott in particular. I should also like to thank Tony Price and Mike Gilbert whose work at Newcastle I have used shamelessly.